The influence of Se content of the seed and the root of Areca catechu by fermenting of Acetobacter–Saccharomyces consortium as an antimicrobial gargle - TITIN YULINERI; ERNAWATI KASIM; NOVIK NURHIDAYAT (Society for Indonesian Biodiversity, 2006)
The research on the using of Areca catechu seeds and roots extract contain selenium which fermented by Acetobacter–Saccharomyces consortium as a gargle had been conducted. The aim of the research was to know the influence of Se content of the seed and the root of Areca catechu by fermenting of Acetobacter–Saccharomyces consortium on the growth of Streptococcus mutans bacteria. The research consisted of four stages i.e. fermented the extract, isolated S. mutans, tested the activity of the antimicrobial and analyzed selenium concentration in the extract. The result showed that the concentration of selenium has fluctuation. The highest content of selenium of the seeds extract at 2.2 g/L concentration was 3.05 ppb on the fifteenth day while on the root extract at 8.8 g/L was 14.03 ppb on the twenty first day fermentation. Both of the extract has potential used as antiseptic gargle. The antimicrobial agents could inhibit the growth of S. mutans better than the three kinds of commercial gargles. © 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: selenium, Areca catechu, Acetobacter, Saccharomyces, Streptococcus mutans, antimicrobial, gargle